Security and Religious Radicalization. Securitization of Islam in Europe (Stato, Chiese e pluralismo confessionale, 2018)
SUMMARY: 1. Introduction - 2. General measures of the anti-terrorist laws; social surveillance and immigration control - 3. Antiterrorist laws and Islam: the securitization of Muslims in western countries - 4. The enforcement of measures affecting Muslim population not directly related to security: the vague criminalization of Islam - 5. Effects of the measures direct or indirectly justified on security reasons in religious freedom; specially related to Muslim population - 6. Closing remarks; positive statements in the construction of the European Union framework.